Research on AUV underwater landing strategy based on variable buoyancy system - SUN Qinggang; ZHENG Rong; YANG Bin; LI Mozhu (Zhongguo Jianchuan Yanjiu, 2018)
[Objectives] The underwater landing of an Autonomous Underwater Vehicle(AUV)is a way to achieve underwater long-term latency and fixed-point observation which is conductive to the better control of changes in the marine environment.[Methods] This paper mainly introduces the fundamental structure and main functions of an AUV which is based on the oil sac type variable buoyancy system. Two kinds of underwater landing strategies are established:controlled buoyancy vertical dive landing and sailing dive and controlled buoyancy vertical landing. The target point deviation,energy consumption and AUV take-off from the bottom are analyzed,and the actual underwater landing experimental verification is carried out in a lake.[Results] The experimental results show that the AUV is able to steadily land underwater and take off from the bottom safely with this variable buoyancy system. The control strategy of sailing dive and controlled buoyancy vertical landing can save more energy,and the landing point is more accurate than with the strategy of controlled buoyancy vertical diving.[Conclusions] As such,the control strategy of sailing dive and controlled buoyancy vertical landing is more in line with the demands of future practical application.